2021
DOI: 10.1080/20905068.2021.1952821
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and distribution of cephalosporin resistance determinants in Escherichia coli and Klebsiella pneumoniae isolated from patients attending Kampala International University Teaching Hospital in Bushenyi, Western Uganda

Abstract: View related articlesView Crossmark data Molecular characterization and distribution of cephalosporin resistance determinants in Escherichia coli and Klebsiella pneumoniae isolated from patients attending

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
3
3
2
Order By: Relevance
“…Besides, our ndings indicated a high proportion of K. pneumoniae isolates were ESBL producers, which corroborates earlier reports from Kenya [53], [54], Uganda [35], [36], [55], Tanzania [33], Ethiopia [34], and Nepal [40], [41]. Notably, previous reports from Kenya [31], [56], Tanzania [46], Uganda [45], Ethiopia [57], Nigeria [37], Burkina Faso[38], Chad [39], Iran [50], Nepal [51], Thailand [48], Brazil [49], and the USA [58] showed that the proportion of ESBL-producing K. pneumoniae isolates was lower than that which we report herein. These differences may be due to disparities in infection prevention control protocols, local antimicrobial treatment guidelines, abuse of broadspectrum antibiotics and third generation cephalosporins, geographical dynamics, hospitalisation, and the presence and effectiveness of antimicrobial stewardship committees at various health facilities in various territories [59].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Besides, our ndings indicated a high proportion of K. pneumoniae isolates were ESBL producers, which corroborates earlier reports from Kenya [53], [54], Uganda [35], [36], [55], Tanzania [33], Ethiopia [34], and Nepal [40], [41]. Notably, previous reports from Kenya [31], [56], Tanzania [46], Uganda [45], Ethiopia [57], Nigeria [37], Burkina Faso[38], Chad [39], Iran [50], Nepal [51], Thailand [48], Brazil [49], and the USA [58] showed that the proportion of ESBL-producing K. pneumoniae isolates was lower than that which we report herein. These differences may be due to disparities in infection prevention control protocols, local antimicrobial treatment guidelines, abuse of broadspectrum antibiotics and third generation cephalosporins, geographical dynamics, hospitalisation, and the presence and effectiveness of antimicrobial stewardship committees at various health facilities in various territories [59].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, surveys conducted in other countries, including Rwanda [32], Tanzania [33], Ethiopia [34], Uganda [35], [36], Nigeria [37], Burkina Faso [38], Chad [39], and Nepal [40]; [41] revealed a similar pattern of ESBL production in E. coli isolates. However, the proportion of ESBL-producing E. coli isolates in this study was lower than that reported in Kenya [42], [43], Uganda [44], [45], Tanzania [46], Canada [47], Thailand [48], Brazil [49], Iran [50], Nepal [51], the USA, Europe, Asia-Paci c, and Latin America [52]. Besides, our ndings indicated a high proportion of K. pneumoniae isolates were ESBL producers, which corroborates earlier reports from Kenya [53], [54], Uganda [35], [36], [55], Tanzania [33], Ethiopia [34], and Nepal [40], [41].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Besides, our findings indicated a high proportion of K. pneumoniae isolates were ESBL producers, which corroborates earlier reports from Kenya [ 56 , 57 ], Uganda [ 41 , 42 , 58 ], Tanzania [ 4 ], Ethiopia [ 40 ], and Nepal [ 46 , 47 ]. Notably, previous reports from Kenya [ 38 , 59 ], Tanzania [ 5 ], Uganda [ 51 ], Ethiopia [ 60 ], Nigeria [ 43 ], Burkina Faso [ 44 ], Chad [ 45 ], Iran [ 14 ], Nepal [ 54 ], Thailand [ 53 ], Brazil [ 18 ], and the USA [ 61 ] showed that the proportion of ESBL-producing K. pneumoniae isolates was lower than that which we report herein. These differences may be due to disparities in infection prevention control protocols, local antimicrobial treatment guidelines, abuse of broad-spectrum antibiotics and third generation cephalosporins, geographical dynamics, hospitalisation, and the presence and effectiveness of antimicrobial stewardship committees at various health facilities in various territories [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 E. coli has been implicated in both nosocomial and community-acquired infections, including respiratory tract infections, urinary tract infections, and enteric infections in Uganda and beyond. 8 , 9 E. coli’s threat is mainly attributed to its ability to rapidly acquire antibiotic resistance through multiple mechanisms. 10 Whereas evidence globally indicates the presence of E. coli in the environment and animals.…”
Section: Introductionmentioning
confidence: 99%